Profile of Characteristics, Severity, Location, Lesion Size, and Stress Levels in Patients with Lichen Simplex Chronicus at the Teaching Hospital of Andalas University - Muflihati Nurzain; Rina Gustia; Rini Gusya Liza; Ennesta Asri; Taufik Ashal; Abdiana (Faculty of Medicine, Universitas Airlangga, 2026)
Background: Lichen simplex chronicus (LSC) is a form of eczema that damages the skin barrier due to chronic itching. Stress is a contributing factor, leading to a persistent itch–scratch cycle that worsens lesion appearance and size. Purpose: This study aimed to describe the characteristics, severity, lesion location, and size, as well as stress levels, in patients with LSC. Methods: This descriptive cross-sectional study involved 42 LSC patients from the Dermatology and Venerology Outpatient Clinic at Andalas University Teaching Hospital, diagnosed between August 2019 and August 2023. Samples were selected using simple random sampling. Severity was measured using the EASI score, lesion location was based on medical records, lesion size was measured with a tape, and stress level was assessed using the PSS-10 questionnaire. Data were analyzed using univariate analysis (age, gender, occupation, severity, lesion location, and size). Result: The majority of LSC cases occurred in the 56–65 age group (42.9%), predominantly in women (57.1%), with civil servants being the most common occupation (28.6%). Most patients had mild to moderate severity (40.5%), with the ankle as the most frequent lesion site (26.2%), plaque as the most common lesion type (90.5%), and moderate stress being most prevalent (57.1%). Conclusion: Most patients were aged 56–65, predominantly female, and civil servants. Lesions were mainly mild to moderate in severity, commonly located on the ankle, with the plaque-type being most frequent. Moderate psychological stress was most prevalent.